2021
DOI: 10.3897/folmed.63.e53060
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on phytochemical composition and memory enhancing effect of Ginkgo biloba seed extract

Abstract: Introduction: The Ginkgo biloba L. tree is considered as one of the oldest species on Earth. It is known as a “living fossil” dating back approximately 200 million years. Both the leaves and seeds of this tree have been used for millennia in traditional Chinese medicine. Aim: To study the phytochemical profile of Gingko biloba seed extract (GBSE) and its memory enhancing effects. Materials and methods: Liquid chromatography with mass detection (LC-MS) was performed for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(43 reference statements)
2
8
0
Order By: Relevance
“…Our data from chromatographic analysis, as well as data from other authors, confirm that the terpene trilactones in seed extract are in greater quantities than flavonoids, and it could have healing properties similar to leaf extract. In a recent study, we confirmed that this extract enhances learning and memory functions in rats and has an effect comparable to that of the nootropic medication Piracetam [28].…”
Section: Discussionsupporting
confidence: 70%
“…Our data from chromatographic analysis, as well as data from other authors, confirm that the terpene trilactones in seed extract are in greater quantities than flavonoids, and it could have healing properties similar to leaf extract. In a recent study, we confirmed that this extract enhances learning and memory functions in rats and has an effect comparable to that of the nootropic medication Piracetam [28].…”
Section: Discussionsupporting
confidence: 70%
“…The extract was centrifuged at 6000× g for 10 min, and the supernatant was separated. The extraction was carried out two more times, using 70% methanol as an extractant [4]. Thereafter, the combined extracts were evaporated at 30 • C under a vacuum [4].…”
Section: Preparation Of Ginkgo Biloba Seed Extract (Gbse)mentioning
confidence: 99%
“…The extraction was carried out two more times, using 70% methanol as an extractant [4]. Thereafter, the combined extracts were evaporated at 30 • C under a vacuum [4]. The amount of dry matter obtained was determined gravimetrically.…”
Section: Preparation Of Ginkgo Biloba Seed Extract (Gbse)mentioning
confidence: 99%
See 2 more Smart Citations